2018
DOI: 10.1152/ajpregu.00425.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise in a cold environment on transcriptional control of PGC-1α

Abstract: Peroxisome proliferator-activated receptor-α coactivator-1α (PGC-1α) mRNA is increased with both exercise and exposure to cold temperature. However, transcriptional control has yet to be examined during exercise in the cold. Additionally, the need for environmental cold exposure after exercise may not be a practical recovery modality. The purpose of this study was to determine mitochondrial-related gene expression and transcriptional control of PGC-1α following exercise in a cold compared with room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
(81 reference statements)
5
19
0
Order By: Relevance
“…In this same manner, exercise increases heat production and may limit any cold related response. Indeed, our data indicate an increase in core temperature during exercise with only very minimal differences between environments, which is supported by previous literature [23,29]. This core temperature response could explain the limited effect of environmental temperatures observed in the current study on CIRP and RBM3 mRNA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this same manner, exercise increases heat production and may limit any cold related response. Indeed, our data indicate an increase in core temperature during exercise with only very minimal differences between environments, which is supported by previous literature [23,29]. This core temperature response could explain the limited effect of environmental temperatures observed in the current study on CIRP and RBM3 mRNA.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that thermos-reception from the skin may ultimately lead to a differential mRNA response and that skeletal muscle mRNA may be altered. Indeed, we have previously observed an altered mRNA response to exercise in different environmental temperatures when core temperature was unaltered [23].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…More specifically, aerobic exercise paired with environmental cold exposure has been shown to upregulate the transcription of PGC-1α [ 5 , 6 ]. Some studies have not detected a statistically significant upregulation of PGC-1α in the cold compared to control conditions but did observe non-statistical effects [ 7 , 8 , 9 , 10 ]. Taken collectively, it appears that environmental cold interventions during aerobic exercise enhance the exercise-induced transcription of PGC-1α in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relation between FOXO1 and PGC‐1α remains unclear. It has been reported that FOXO1 could directly bind to the PGC‐1α promoter and trigger the transcription of PGC‐1α in liver and muscle tissues (Ropelle et al, ; Shute, Heesch, Zak, Kreiling, & Slivka, ). But up‐regulated FOXO1 was accompanied by a reduction of PGC‐1α, while PGC‐1α overexpression suppressed the activation of FOXO1 and FOXO3 in muscle (Kang & Ji, ).…”
Section: Discussionmentioning
confidence: 99%